2018
DOI: 10.3389/fchem.2018.00616
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces Between Cathode and Electrolyte in Solid State Lithium Batteries: Challenges and Perspectives

Abstract: Solid state lithium batteries are widely accepted as promising candidates for next generation of various energy storage devices with the probability to realize improved energy density and superior safety performances. However, the interface between electrode and solid electrolyte remain a key issue that hinders practical development of solid state lithium batteries. In this review, we specifically focus on the interface between solid electrolytes and prevailing cathodes. The basic principles of interface layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
145
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 116 publications
(168 reference statements)
1
145
0
3
Order By: Relevance
“…The high‐voltage compatibility represents the capability of electrolyte to restrain oxidative decomposition. Thermodynamically, as shown in Figure , a high‐voltage‐stable SPE means all the components of polymer electrolyte (polymer, lithium salts, and additives) must simultaneously have lower energy level of highest occupied molecular orbital (HOMO) than cathode potential ( µ c ) . However, due to the strong and complicated oxidation state of the cathode materials during lithium deintercalation process, µ c could shift down to the lower state than the HOMO of SPEs, resulting an interfacial parasitic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The high‐voltage compatibility represents the capability of electrolyte to restrain oxidative decomposition. Thermodynamically, as shown in Figure , a high‐voltage‐stable SPE means all the components of polymer electrolyte (polymer, lithium salts, and additives) must simultaneously have lower energy level of highest occupied molecular orbital (HOMO) than cathode potential ( µ c ) . However, due to the strong and complicated oxidation state of the cathode materials during lithium deintercalation process, µ c could shift down to the lower state than the HOMO of SPEs, resulting an interfacial parasitic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Famprikis et al [51] and Zhang et al [116] reported on the fundamentals of electrolytes and Oudenhoven et al [117], Julien and Mauger [60], and Rambabu et al [118] reviewed the technology of solid-state microbatteries. Moreover, in situ and ex situ techniques were explored for elucidating the solid electrode/electrolyte interfaces [40,67,80,98,[119][120][121][122][123] and computational methods were reviewed by Xiao et al [94] for understanding the conduction mechanisms in both oxide and sulfide electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the materials research community is wholly engaged in enabling the necessary radical departure(s) from conventional SIB technology. The replacement of the ubiquitous liquid electrolyte in commercial SIB with a solid-state electrolyte (SSE), the new battery configuration being termed an "all-solidstate battery" (ASSB), represents one such paradigmatic shift in energy storage technology (Nie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%